2001
DOI: 10.1038/35083537
|View full text |Cite
|
Sign up to set email alerts
|

A possible nitrogen crisis for Archaean life due to reduced nitrogen fixation by lightning

Abstract: Nitrogen is an essential element for life and is often the limiting nutrient for terrestrial ecosystems. As most nitrogen is locked in the kinetically stable form, N2, in the Earth's atmosphere, processes that can fix N2 into biologically available forms-such as nitrate and ammonia-control the supply of nitrogen for organisms. On the early Earth, nitrogen is thought to have been fixed abiotically, as nitric oxide formed during lightning discharge. The advent of biological nitrogen fixation suggests that at som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
195
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(201 citation statements)
references
References 22 publications
5
195
1
Order By: Relevance
“…Of these, CO 2 has a direct volcanic source, while elemental sulphur (as just discussed) and sulphate can form through the photolysis of SO 2 in the atmosphere. An early primary source of nitrate was also probably through the oxidation of N 2 by lightning (Yung & McElroy 1979;Navarro-González et al 2001). The electron donors and electron acceptors which become available as products of secondary anaerobic metabolisms are listed in table 3.…”
Section: Early Energy and Possible Community Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Of these, CO 2 has a direct volcanic source, while elemental sulphur (as just discussed) and sulphate can form through the photolysis of SO 2 in the atmosphere. An early primary source of nitrate was also probably through the oxidation of N 2 by lightning (Yung & McElroy 1979;Navarro-González et al 2001). The electron donors and electron acceptors which become available as products of secondary anaerobic metabolisms are listed in table 3.…”
Section: Early Energy and Possible Community Structurementioning
confidence: 99%
“…We can identify a primary source of oxidized nitrogen (NO) from lightning (Yung & McElroy 1979;Navarro-González et al 2001) and of ammonia from the reduction of N 2 at high temperatures in mid-ocean ridge hydrothermal circulation systems (Brandes et al 1998a,b). In addition, there is the possibility of biological nitrogen fixation, fixing atmospheric N 2 to ammonia for use in biomolecules.…”
Section: Nitrogen-based Ecosystemmentioning
confidence: 99%
“…It has previously been proposed that a diminishing supply of abiotically fixed nitrogen resulted in a "nitrogen crisis" in the Neoarchean and triggered the invention of the nitrogenase enzyme (Navarro-Gonzalez et al, 2001). It has further been suggested (Boyd et al, 2011b) that the first nitrogenase enzymes responsible for nitrogen fixation in the early biosphere were "proto-nitrogenases" ancestral to the current forms and thus not as specific or efficient at reducing unreactive N 2 to bioavailable NH 3 .…”
Section: Was There An Archean 'Nitrogen Crisis'?mentioning
confidence: 99%
“…Also, Chameides et al [1979], in their simulations of the Venus atmosphere, report a yield of production of NO that is nearly 2 orders of magnitude below that of CO. In a laser plasma experiment made in a CO 2 -N 2 mix it is reported that for a mixing ratio of 0.98 the CO yield obtained is 200 times that of NO [Navarro-González et al, 2001]. Even though we could not measure the NO yield we can nevertheless estimate an upper limit for it at 1 × 10 16 molecules J −1 .…”
Section: Discussionmentioning
confidence: 79%